The Categorical Analysis of the Concepts «Self-Realization» and «Professional Self-Realization» - Prus, Alla (Pedagogical Discourse, 2016)
The article presents the results of a study of the categories of «self-realization» and «professional self-realization». Based on the review of psychological and pedagogical sources and summarize various approaches to semantic consideration it clarified analyzed concepts. Such definitions as «self-actualization» and «professional self-realization», were formulated, which, in our opinion, characterize their basic concepts. They also most closely correspond the directions of our research. Using the method of content analysis were analyzed some concepts in 46 scientific sources (abstracts, monographs, articles in national and international professional journals, etc.). Special attention was paid to the works of recent years. The study identified a variety of approaches in substantial consideration of the analyzed concepts. Logical-system analysis allowed to identify the conception of «self-realization» and «professional self-realization» in scientific sources and based on that made a categorical analysis of the concepts which are studying. It were identified some prospects of further research such as, the study of the levels of development of professional self-realization of future teachers of fine arts; substantiation of the structural-dynamic model of formation of professional self-realization of future teachers of fine art based on certain concepts etc. Key words: self-realization, professional self-realization, categorical analysis of the concept of professional self-realization of the future teacher of fine arts, development, incentive-essential motivational forces of human, creative activity, co-creation.